The Influence of Organizational Culture and Individual Characteristic on Employee Job Satisfaction at PT. Garuda Indonesia (Persero) Tbk Medan - Asrizal Efendy Nasution; Muhammad Taufik Lesmana (Journal of International Conference Proceedings (JICP), 2019)
The purpose of this study was to determine and analyze the influence of organizational culture and individual characteristic on employee job satisfaction at PT. Garuda Indonesia (Persero) Tbk Medan both partially and simultaneously. The population in this study were all employees of PT. Garuda Indonesia (Persero) Tbk Medan, amounting to 35 people. The sample used is a saturated sample given the relatively small population. Data analysis technique used is multiple linear regression. Based on the results of the study, organizational culture and individual characteristic both partially and simultaneously have a positive and significant effect on employee work satisfaction at PT. Garuda Indonesia (Persero) Tbk Medan.